Identifying the Relationship of Food Addiction, Impulsiveness and Loneliness with Different Variables in University Students - Dincyurek, Hazal; Alasya, Muzeyyen; Kagan, Sertan (Modestum Ltd, 2018)
The term food addiction is rapidly attracting interests of psychologists as the evidence of the similarities between substance and food dependency has been increasing. It is important to find out what is associated with food addiction as it may lead to serious health conditions that can threaten people's lives. In this study, food addiction was examined to see if there is a significant relationship between impulsivity and loneliness. Total of 376 (216 male and 160 female) university students participated in Northern Cyprus. Turkish version of Yale Food Addiction Scale, Turkish version of UCLA Loneliness Scale and Turkish version of Barratt Impulsiveness Scale was used. It was found that there was a significant relationship between food addiction and impulsivity, as well as food addiction and loneliness.
Keywords: food addiction; impulsiveness; loneliness; university students